The Consequences of Poor Communication during Hospital to Skilled Nursing Facility Transitions: A Qualitative Study - King, Barbara J. (2013)
BACKGROUND: Nurses in skilled nursing facilities (SNFs) play a key role in initiating/transitioning care for the >5 million patients who transition from hospitals-to-SNFs annually. Although hospital discharge processes are well studied, little is known about the SNF nursing processes or the SNF-based consequences of variation in transitional care quality. OBJECTIVE: To examine how SNF nurses transition the care of patients admitted from hospitals, the barriers they experience, and the outcomes associated with variation in the quality of transitions. DESIGN: Qualitative study using grounded dimensional analysis, focus groups and in-depth interviews. SETTING: 5 Wisconsin SNFs. PARTICIPANTS: 27 registered nurses. RESULTS: SNF nurses rely heavily on written hospital discharge communication to effectively transition patients into the SNF. Nurses cited multiple inadequacies of hospital discharge information, including regular problems with medication orders (including the lack of opioid prescriptions for pain), little patient psychosocial/functional history, and inaccurate information regarding current health status. These communication inadequacies necessitated repeated phone clarifications, created care delays (including delays in pain control), increased SNF staff stress, frustrated patients/family members, directly contributed to negative SNF facility image, and increased a patient's rehospitalization risk. SNF nurses identified a specific list of information/components that they need to facilitate a safe, high-quality transition. CONCLUSION: Nurses note multiple deficiencies in hospital-to-SNF transitions, with poor quality discharge communication being identified as the major barrier to safe and effective transitions. This information should be used to refine and support the dissemination of evidence-based interventions which support transitions of care, including the Interventions to Reduce Acute Care Transfers II (INTERACT) program.